Two nights [compact disc, unabridged] : a novel - Reichs, Kathy (Penguin Random House, 2017)
Sunday Night is a talented, tough woman with physical and psychological scars and a killer instinct. She has spent years running from her past. But after a bomb explosion leaves a girl missing, the family needs Sunnie's help. And it might just lead her to the truth about herself.